MEMBANGUN CITRA DIRI POSITIF MELALUI PEMBELAJARAN TENTANG PERSONAL BRANDING UNTUK GENERASI Z - Wulan Purnama Sari; Claribel Halim; Fiona CH Bernadett (Jurnal Bakti Masyarakat Indonesia, 2025)
Generation Z is known as digital natives who are deeply connected to social media and information technology. Their involvement in the digital space has influenced various aspects of life, including the process of identity and self-image formation. Unlike previous generations who developed their identities through direct, face-to-face interactions, Generation Z is more heavily influenced by what they consume and present on social media. This creates its own set of challenges, such as identity crises, social anxiety, and pressure to meet digitally constructed social standards. In response to these issues, this Community Service Program (PKM) was carried out to provide education on the importance of personal branding as a strategy to build a positive and authentic self-image. The program was implemented at SMKN 1 Cimahi through three main phases: pre-implementation (audience engagement and initial survey), implementation (material delivery and interactive discussions), and post-implementation (evaluation, documentation, and publication). The interactive counseling method was chosen to encourage active student participation in understanding and practicing the concept of personal branding. Evaluation results showed an increase in participants' understanding of the importance of building an authentic self-image, as well as heightened awareness of digital literacy. This activity not only had a positive impact on the participants but also supported the school’s role in fostering student character development and readiness to face the challenges of the digital world. Moving forward, similar activities are expected to continue, with a focus on advanced digital literacy and the productive use of social media.